Bone regeneration driven by a nano-hydroxyapatite/chitosan composite bioaerogel for periodontal regeneration - Souto-Lopes, M.; Grenho, L.; Manrique, Y.; Dias, M. M.; Lopes, J. C. B.; Fernandes, M. H.; Monteiro, F. J.; Salgado, C. L. (Frontiers in Bioengineering and Biotechnology, 2024)
The most recent progresses for reconstructive therapy for the management of periodontitits and peri-implantitis bone defects have been relying on the development of highly porous biodegradable bioaerogels for guided bone regeneration. The objective of this work was to evaluate in vitro the osteoinduction of periodontal-originating cells (human dental follicle mesenchymal cells, DFMSCs) promoted by a nanohydroxyapatite/chitosan (nHAp/CS) bioaerogel, which was purified and sterilized by a sustainable technique (supercritical CO2). Moreover, the in vivo bone regeneration capacity of the nHAp/CS bioaerogel was preliminarily assessed, as a proof-of-concept, on a rat calvaria bone defect model. The quantification of DNA content of DFMSCs seeded upon nHAp/CS and CS scaffolds (control material) showed a significant increase from the 14th to the 21st day of culture. These results were corroborated through confocal laser scanning microscopy analysis (CLSM). Also, the alkaline phosphatase (ALP) activity increased significantly at the 21st day, similarly for both materials. Moreover, the presence of nHAp promoted a significantly higher expression of the osteogenic genes after 21 days when compared to CS scaffolds and control. CLSM images of 21 days of culture also showed an increased deposition of OPN over the nHAp/CS surface. The in vivo bone formation was assessed by microCT and by histological analysis. The in vivo evaluation showed a significant increase in bone volume in the nHAp/CS test group when compared to CS and the empty control, as well as higher new bone formation and calcium deposition within the nHAp/CS structure. Overall, the present study showed that the nHAp/CS bioaerogel can offer a potential solution for periodontal and peri-implant bone regeneration treatments, since the in vitro results demonstrated that it provided favorable conditions for the DFMSCs proliferation and osteogenic differentiation, while the in vivo outcomes confirmed that it promoted higher bone ingrowth.